Nitrogen Dynamics and Influence of Soil Properties in Calcareous Soils of Saurashtra Region of Gujarat, India - N.B. Misal; P. Sukul; K.B. Polara (Journal of the Indian Society of Soil Science, 2023)
The majority of medium black soils of Saurashtra region of Gujarat, India are calcareous in nature derived from trap basalt in semi-arid climate. Almost 10 agro-ecological situations of Saurashtra region have been identified which vary in soil resource. One hundred sixty nine surface soil samples were collected (0-15 cm) at an interval of 10 years and N status in respect of its different fractions were determined. The experimentation on various soil groups of Saurashtra revealed that the available N content in general improved from 54.69 to 58.44 ppm, total N from 0.034 to 0.035% and organic carbon from 0.44 to 0.45%, while ammonical N declined from 7.49 to 7.39 ppm and nitrate N from 3.16 to 3.09 ppm in the span of 10 years interval. Whole set of data from 10 different soil groups of Saurashtra region was subjected to statistical analysis including correlation among the fractions and various soil physicochemical properties. Available N exhibited a significant positive relationship with other forms of N in all soil groups except soil groups deep black trap basalt (DBTB) and stony, where the relationship was not significant. As far as soil properties are concerned, different soil groups rendered obviously a variegated picture. The available N showed a significant positive relationship with soil electrical conductivity (EC) and exchangeable sodium percentage (ESP) in soil group medium black trap basalt (MBTB) and only with soil EC in soil group medium black lime stone (MBLS). However, a significant negative relationship was exerted by available N to soil pH and soil cation exchange capacity (CEC) in soil group MBLS.